Management of facet joints osteoarthritis associated with chronic low back pain: A systematic review. Issue 6 (December 2021) - Baroncini, Alice; Maffulli, Nicola; Eschweiler, Joerg; Knobe, Matthias; Tingart, Markus; Migliorini, Filippo
Abstract: Introduction: Facet joint injections (FJI) and medial branch blocks (MBB) can be employed for chronic low back pain (LBP) using different drugs such as corticosteroids, hyaluronic acid, sarapin and local anaesthetics. This systematic review compares the results of injections obtained with different compounds in the management LBP originating from facet joints. Methods: The present systematic review was conducted according to the PRISMA statement. The literature search was performed in October 2020. All the randomized clinical trials concerning injection treatments for chronic LBP. Drugs rather than steroids, hyaluronic acid, anaesthetics and sarapin were not considered, as well as those reporting outcomes from combined treatments. The Oswestry Disability Index (ODI) and the numeric rating scale (NRS) were retrieved. Results: Data from 587 patients were retrieved. The mean follow-up was 12.4 ± 10.5 months. The mean age was 51.3 ± 9.6 years old. 57% (335/587) of patients were women. Steroids promoted a reduction of NRS by 28% ( P < 0.0001) and an improvement of the ODI by 13.2% ( P = 0.005), and local anaesthetics produced an improvement of the ODI by 9.8% ( P < 0.0001). Sarapin resulted in a reduction of NRS by 44% ( P = 0.04) and an improvement the ODI by 14.9% ( P = 0.004); sarapin combined with steroids promoted a reduction of NRS by 47% ( P = 0.04) and an improvement of the ODI by 11.7% ( P = 0.001). Conclusion: Injections for chronic LBP deriving from facet joints osteoarthritis are encouraging, especially when considering MBB. Level of evidence: I, systematic review of RCTs.